Similarities and Differences Between the Albanian and English with Regard to the Word Formation Process - Shahini, Miranda; Memisha, Valter (Mediterranean Journal of Social Sciences, 2011)
During recent decades the links between Albanian and English have increased steadily. English as an international language,even as a first language in the society with which the Albanian is faced in every field life ,scientific, economic, cultural, political, military,etc. is the object of study with much interest to be treated and to be observed from different and inclusive denominations. The lexicon ofstandard Albanian, as well as that of the English can be surveyed from several directions: it can be analyzed by examining the lexicallayers that make it up, and the functions they perform can be studied in the entire system of language, the internal development processesand movements that occur can be detected, morpho-semantic and stylistic processes of various word-formation methods can be treated etc.The aim of the paper is to analyse and compare Albanian and English by the word formation viewpoint. The paper highlights theaffixed formations , finding similarities and differences in this area.